Perancangan Sistem Kendali Untuk Penyiraman dan Pemupukan Lahan Pertanian Berbasis Smartphone - Purnama Irwan; Romiyadi Romiyadi; Adi Febrianton; Purnama Putri, Indah; Dwianda, Yudi (Jurnal Sains dan Ilmu Terapan, 2025)
ChatGPT said: The processes of irrigation and fertilization in agriculture are time-consuming and physically demanding, as farmers typically irrigate twice daily and fertilize every three to four days. These repetitive tasks can lead to fatigue and reduced efficiency. To address this, we have developed an automated system for irrigation and fertilization that enables farmers to manage these activities remotely via smartphone. The system utilizes a microcontroller programmed based on specific agricultural needs and connected to the internet through Wi-Fi. This connectivity allows farmers to activate irrigation or fertilization with a single tap on their smartphones, anytime and from anywhere. The system aims to increase efficiency, reduce labor, and provide a more cost-effective and precise method of managing agricultural land. By automating routine tasks, farmers can better allocate their time and energy while ensuring optimal crop growth. The final outcome of this research is expected to be applicable directly in the field, allowing for real-world testing and refinement. Furthermore, the findings will be shared through a scientific publication to support knowledge.